Historical and Ethnological Studies of the “Author's Song” (Bardic) (Journal of Pedagogical Inventions and Practices, 2022)
The article describes the need to study the author's song in its historical formation in the context of Russian poetry of the 1950s-1960s and, in this regard, to consider a number of features of the song and poetic culture that preceded the birth of this phenomenon. The main goal of the study is to determine the place and significance of the author's song as a poetic phenomenon in the context of modern national culture. At the same time, taking into account the important fact that the boundaries of the study are determined solely by the period of the origin and crystallization of the genre (1950-1960), the circle of goals and objectives organically included, firstly, the clarification of the causes, prerequisites and conditions for the formation of the named phenomenon, and secondly, coverage of the problem and interaction with other song and poetic phenomena in order to include common typological features.